Diagnostic Considerations of Venous Thromboembolic Disease. Issue 3 (July 2017) - Alhassan, Sulaiman; Leap, Jennifer; Popuri, Anand; Yadam, Suman; Singh, Anil C.; Balaan, Marvin
Abstract : Venous thromboembolism (VTE) includes deep venous thrombosis (DVT) and pulmonary embolism (PE). The clinical presentation of VTE is nonspecific and requires confirmatory testing. The most common diagnostic tool for DVT is duplex ultrasonography since it is a noninvasive test with high accuracy. Contrast venography is considered the gold standard modality to diagnose DVT, but it is an invasive test. Magnetic resonance venography and computed tomography venography are alternative diagnostic methods for DVT, which can be helpful in certain circumstances. Pulmonary embolism is commonly diagnosed by computed tomography pulmonary angiography. Ventilation perfusion scanning is an alternative imaging to diagnose PE in patients who cannot receive intravenous contrast. Pulmonary angiography is still the gold standard in the diagnosis of PE and is usually needed in specific conditions. D-dimer assay can be utilized in ruling VTE out in low-risk patients. Estimating the pretest clinical probability for having VTE is the key step in guiding the clinicians and nurses to the appropriate diagnostic method for patients with suspected DVT or PE.